2017
DOI: 10.2177/jsci.40.21
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of 7 cases of familial mediterranean fever

Abstract: summary Background: Familial mediterranean fever (FMF) is a single inherited autoinflammatory disease characterized by periodic fever with relatively short duration of 1 to 3 days and sterile serositis. Although the prevalence rate is highest in the Mediterranean coastal area, a large number of cases have been reported recently by genetic analysis by identification of MEFV (Mediterranean fever) which is responsible gene in Japan too. In outpatient department of rheumatology, diagnosis and treatment of FMF is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Recently, more case reports of FMF patients have been published in Japan. Ogita et al ( 18 ) recently reported seven Japanese cases of FMF which all carried MEFV mutations and responded well to colchicine treatment. Kinoshita et al ( 19 ) presented a case of Mollaret meningitis with an MEFV mutation, which showed a similar clinical course to our case 2.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more case reports of FMF patients have been published in Japan. Ogita et al ( 18 ) recently reported seven Japanese cases of FMF which all carried MEFV mutations and responded well to colchicine treatment. Kinoshita et al ( 19 ) presented a case of Mollaret meningitis with an MEFV mutation, which showed a similar clinical course to our case 2.…”
Section: Discussionmentioning
confidence: 99%
“…Familial Mediterranean fever (FMF) is an autoimmune disease caused by mutations in the MEFV gene and is characterized by periodic fever associated with peritonitis, pleuritis, and arthritis. Prevalent mutation sites in the MEFV gene are known to vary by race, and approximately 500 patients with FMF have been reported in Japan 1 . Gastrointestinal mucosal damage in FMF is rare; however, gastrointestinal lesions resembling inflammatory bowel disease have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalent mutation sites in the MEFV gene are known to vary by race, and approximately 500 patients with FMF have been reported in Japan. 1 Gastrointestinal mucosal damage in FMF is rare; however, gastrointestinal lesions resembling inflammatory bowel disease have been reported. In patients with atypical inflammatory bowel disease, periodic fever, and joint symptoms, FMF should be considered for differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…So far, reports on more than 4,000 patients with FMF have been published worldwide. Approximately 500 FMF patients have been reported in Japan, and the number of such patients has recently tended to increase (1). Patients who have FMF usually present to hospital with abdominal pain and fever.…”
Section: Introductionmentioning
confidence: 99%